Accounting and Financial Innovation: Impacts on Consumer Behavior and the Digitalization Process - Shaker, Mohammad; Jamil , Ahmad (International Journal of Business Management and Entrepreneurship, 2025)
The growing trend of digitalization within business units has significantly influenced various professional fields, including accounting and auditing. This study aims to examine the impact of digitalization on independent auditors and auditing firms in Iran. Employing a qualitative research design, the study utilized a three-stage coding process—open, axial, and selective coding—alongside a grounded theory approach to analyze the collected data. The research population consisted of all auditing firms affiliated with the Iranian Association of Certified Public Accountants. Purposeful sampling was used to select expert participants (certified accountants), and interviews continued until theoretical saturation was achieved. In total, 20 semi-structured interviews were conducted across 13 auditing firms. Findings reveal that digitalization enhances the auditor's role and effectiveness as a governance mechanism, improves audit procedures and methodologies, and increases the quality of accounting information. It also positively influences stakeholder decision-making, recruitment policies, and prompts revisions to standards and legal requirements to align with digital advancements. Furthermore, digitalization improves information security by eliminating paper archives and facilitating better access and transfer of data. However, it also poses security risks by enabling easier disclosure and potential cyber misuse, highlighting the critical need for robust security frameworks to safeguard sensitive information.